Does emotion processing ability mediate the relationship between psychopathy and group psychotherapy engagement? - Casey, H (2013)
Therapeutic engagement in psychopathy is an important area of study due to reports of poor engagement leading to poor treatment outcome for this group. One factor that may influence effective engagement is the ability to process emotional information, which has been shown to be impaired in psychopathy. The study investigated the association between engagement in group therapy and level of psychopathy and assessed whether this relationship is mediated by emotion processing ability. It was hypothesised that higher levels of psychopathy would be associated with lower levels of therapy engagement; however, this relationship would be mediated by four emotion processing indicators believed to be important for good treatment outcome. Specifically, awareness and arousal of emotion, emotion regulation ability, interpretation bias and ability to transform emotion would: i. jointly mediate the relationship between psychopathy and therapy engagement ii. each uniquely mediate the relationship between psychopathy and therapy engagement. Participants, violent offenders with varying levels of psychopathy, were interviewed in a cross-sectional design. Emotion processing ability was assessed using five computerised tasks each selected to best capture one of the cognitive mechanisms of emotion processing outlined above. Psychopathy was measured using the Psychopathy Check List-Revised. Therapy engagement was assessed by group therapists three months after interview using the Group Emotional Engagement Questionnaire (GEEQ). The GEEQ is a new measure designed, developed and tested as part of this study to measure its dependent variable accurately. Psychometric evaluation of the GEEQ demonstrated high levels of reliability (internal, inter-rater) with between good and adequate validity (convergent, discriminant) and good predictive validity. Mediation analysis revealed high Factor 1 psychopathy (the affective component) was associated with poorer therapy engagement (lower GEEQ scores). Interpretation of emotion and transforming emotion acted as suppressors on this relationship. This may suggest that those with many Factor 1 traits used positive interpretation bias as a defence against experiencing distress (schema overcompensation). This response was resistant to change and gave high Factor 1 participants the appearance of being better engaged in therapy than they were. Reaction time data suggested this phenomenon occurred as an automatic response rather than a conscious effort to impression manage.